Systemic review of strongyle infections in horses across Asia: prevalence, diagnosis, and management - Roselan, Puteri Rose Camelia; Mohd Adzahan, Noraniza; Abdul Aziz, Nor Azlina; Sadiq, Mohammed Babatunde; Md Isa, Nur Mahiza; Abdul Rahim, Zulfitri Naim (Chiang Mai University - Faculty of Veterinary Medicine, 2025)
Strongylosis has been one of the most well-known diseases in the equine world. However, there is a lack of substantial knowledge regarding its prevalence in Asia. Hence, this study systematically reviewed data on strongyle species recorded in Asia and the main risk factors, diagnoses, treatment, and control. Four electronic databases were used to search the publications on strongyle species in Asia, and the inclusion and exclusion criteria were established. The chosen publications were accessed to discuss the risk factors, diagnoses, pathogenesis, treatment, and control in Asian countries. A total of 30 articles published between 2000 and 2024 were included. The main strongyle species reported is the large strongyle, with Strongylus edentatus and Strongylus vulgaris being the most prevalent. Small strongyles (cyathostomins) have become remarkably prevalent throughout the year, with Gyalocephalus sp. as the most pervasive. A diverse species prevalence is documented in the western countries with the weather playing an important role. Strongyles were mostly diagnosed by faecal floatation and quantified by the McMaster method, while further diagnosis was done using molecular techniques. Information on the use of anthelmintic drugs is still lacking. Subsequently, a progressive increase in the knowledge of strongyle species over the years in Asia countries has been noted. With the emergence of anthelmintic resistance, more research should be done, focusing on bridging the knowledge gaps to ensure the health of equine species and minimise economic losses associated with strongyle infections.